Neuraxial Anesthesia in Children With Ventriculoperitoneal Shunts. (July 2018) - Longhini, Anthony B.; Cheon, Eric C.; Hajduk, John; Bowman, Robin; Birmingham, Patrick K.
Abstract : Neuraxial anesthesia has been demonstrated to be safe and effective for children undergoing subumbilical surgery. There is limited evidence regarding the safety of neuraxial anesthesia in pediatric patients with a ventriculoperitoneal shunt. We evaluated a series of 25 patients with indwelling ventriculoperitoneal shunts for complications within 30 days of any procedure performed with a neuraxial technique. One patient required a ventriculoperitoneal shunt revision 5 days after a lumbar catheter placement. The neurosurgeon determined the revision to be likely unrelated to the patient's lumbar catheter. Concerns about the use of neuraxial anesthesia in patients with an indwelling ventriculoperitoneal shunt may be overstated.